Pengaruh Humor Appeals Terhadap Brand Awareness Pada Iklan Televisi - Debby Arisandi (Universitas Muhammadiyah Sumatera Utara, 2017)
Television is a communication network with a role as a mass communication is one-way, causing heterogeneous simultaneity and the communicant. Every day people look at a number of television commercials. There are thousands of products on the market and It would be interesting to know why certain people respond to ads or not. Advertising is a multi-billion dollar industry with one main goal: to persuade people to buy the product. Advertising is an industry that spends a large amount of time and effort to figure out the best strategy to do what they want. Television advertising has a sense part of a series of activities to promote a product that emphasizes the image elements there in through the intermediary of television media.This study aimed to determine the effect of the use of humor in television advertising on brand awareness (brand) of the product. Based on research that has been done, it is known that the humor in the ad has a positive and significant impact on the brand awareness of the product. The result of consumers' assessment of the use of humor in television advertising, including in both categories so that the brand awareness (brand awareness) by consumers is acceptable.